Algorithms of LiFePO4 Batteries Automatic Charge. (2015) - Solomin, E.V.; Topolsky, D.V.; Toposkaya, I.G.
Abstract: A wide variety of rapidly evolving algorithms of lithium-ion battery charge leads to the lack of statistics on the differential coefficient of a specific battery degradation, or in other words, a misunderstanding of the difference in the state of charge after several charge-discharge cycles as compared to a single one. As a solution of the problem the authors propose the usage of a universal integrated algorithm of LiFePO4 batteries charging with initial and final trickle charge, which will both train the battery and reduce the differential coefficient of degradation, as well as allow testing of local grid power which the battery is charging from. This approach, if distributed widely, may give rich statistic information to be used for further improvement of charge algorithms.